Coady, Amanda. L to R Back Tommy and Nicky Boland, Front Mandy Coady and Angie Boland in a Dory - Heritage NL
Amanda Coady provided a picture of (from left to right) Tommy and Nicky Boland in the back of an orange dory and Mandy Coady and Angie Boland in the front of the dory. The rope attached to the front of the dory is being pulled taught. Mandy Coady and Angie Boland each have hands on their respective oars. Nicky Boland is holding Tommy Boland's hand. A white and red boat can be seen floating in the background.